VALUE AT RISK VARIAN KOVARIAN PADA PORTOFOLIO OPTIMAL MULTI INDEX MODEL - Putri, Mely Amara; Sulistianingsih, Evy; Imro'ah, Nurfitri (EPSILON: JURNAL MATEMATIKA MURNI DAN TERAPAN, 2025)
The construction of an optimal portfolio aims to minimize investment risk, with the Multi-Index Model being one method that accounts for multiple factors influencing stock returns. This study analyzes the optimal portfolio allocation and estimates potential losses using the variance-covariance Value at Risk (VaR) method. The study examines seven stocks from different sectors that have consistently been part of the IDX30 index from January 2019 to June 2024. The factors considered include the Jakarta Composite Index (JCI) and the exchange rate of the Indonesian Rupiah against the US Dollar (USD). The results indicate that the optimal portfolio consists of PT Adaro Energy Tbk. (ADRO), PT Bank Central Asia Tbk. (BBCA), and PT Kalbe Farma Tbk. (KLBF), with respective weights of 18.83%, 77.12%, and 4.05%. This portfolio yields a return of 1.22% with a risk level of 4.93%. The VaR calculation at a 95% confidence level indicates a maximum potential loss of 8.11% of the initial investment value.